Peran Sistem Informasi Akutansi (SIA) dalam Informasi Digital E-Commmerce - Sinta Dewi Octavia Sakti; Dwihanus Dwihanus (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The current era of globalization demands that manual data processing is no longer relevant and accurate for companies. This is because errors that occur due to manual processing can no longer be neutralized. Where the information generated by these errors, becomes inaccurate anymore to be used as a basis for decision making. That is why currently the existence of SIA is becoming increasingly important for a company. Initially the existence of this information system was to collect, process, store, calculate, analyze, and disseminate information for specific purposes. However, currently SIA has a very important impact on the company, namely providing added value to its users because it will ultimately have an impact on improving the company's overall performance.